2012
DOI: 10.1103/physrevb.86.014118
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostudy revealing a layered structure in hydrogen-rich KH6under high pressure

Abstract: By adding small amounts of potassium to hydrogen, the energetically preferred compound KH 6 forms above 70 GPa and metalizes within 166 GPa. Two-layered C2/m and C2/c structures of KH 6 discovered here contain H 2 and H 3 units under high pressure. The metallic C2/c phase is found to be a one-dimensional conductor with a conducting hydrogen-bonded network and an insulating potassium chain. The layered hydrogen-dominant compound KH 6 is found to be a good example of pressure-induced metallization, which origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 28 publications
4
54
0
Order By: Relevance
“…In what follows, such a decrease is also observed in the terms of the superconducting transition temperature calculated by using the relation: ∆ m=1 (T C ) = 0, which gives the T C values equal to 72.91 K, 70.73 K, and 55.50 K at 166 GPa, 230 GPa, and 300 GPa, respectively. We also note, that this decreasing behavior of T C is slightly more evident in the case of our results then in the predictions presented in [9], which based on the McMillan formula [16]. Furthermore, results presented in [9] show that for higher electron-phonon coupling constants McMillan formula underestimate the T C values in KH 6 , whereas in the case when λ is close to the weak-coupling limit (λ < 0.3 [17]) the overestimation can be noticed.…”
Section: Numerical Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…In what follows, such a decrease is also observed in the terms of the superconducting transition temperature calculated by using the relation: ∆ m=1 (T C ) = 0, which gives the T C values equal to 72.91 K, 70.73 K, and 55.50 K at 166 GPa, 230 GPa, and 300 GPa, respectively. We also note, that this decreasing behavior of T C is slightly more evident in the case of our results then in the predictions presented in [9], which based on the McMillan formula [16]. Furthermore, results presented in [9] show that for higher electron-phonon coupling constants McMillan formula underestimate the T C values in KH 6 , whereas in the case when λ is close to the weak-coupling limit (λ < 0.3 [17]) the overestimation can be noticed.…”
Section: Numerical Resultssupporting
confidence: 83%
“…We also note, that this decreasing behavior of T C is slightly more evident in the case of our results then in the predictions presented in [9], which based on the McMillan formula [16]. Furthermore, results presented in [9] show that for higher electron-phonon coupling constants McMillan formula underestimate the T C values in KH 6 , whereas in the case when λ is close to the weak-coupling limit (λ < 0.3 [17]) the overestimation can be noticed. This is due to the fact that BCS theory omits the strong-coupling effects, which are present in the Eliashberg theory.…”
Section: Numerical Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, building on Ashcroft's proposals, density functional theory (DFT) calculations were carried out to predict the structures of hydrides with stoichiometries that are not stable at atmospheric conditions, in the hopes of uncovering hitherto unknown superconductors [19]. Since then, numerous theoretical studies have been performed that investigate the phase diagrams of hydrogen doped with the electropositive alkali metals or alkaline earth metals [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], as well as the electronegative element iodine [35,36] under pressure. Experimental work on the hydrides of lithium and sodium confirmed that species with unique stoichiometries such as NaH 3 and NaH 7 can be synthesized in diamond anvil cells, but the phases that have been reported to date do not exhibit superconductivity [21,37].…”
Section: Introductionmentioning
confidence: 99%
“…The first system explored experimentally was silane (SiH 4 ) [17]. Soon after, many others materials have been explored experimentally [18][19][20][21] and theoretically [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. …”
mentioning
confidence: 99%